Resolution of ColE1 dimers requires a DNA sequence implicated in the three-dimensional organization of the cer site. - Summers, D K (1988)
Plasmid ColE1 specifies a recombination site (cer) which participates in the conversion of plasmid dimers to monomers. The uncontrolled accumulation of dimers (and higher oligomeric forms) would otherwise lead to plasmid instability. Exonuclease III-generated deletions have been used to define the left-hand boundary of the cer site. Deletions which have lost up to 60 bp adjacent to the boundary no longer mediate the conversion of plasmid dimers to monomers, but still recombine with a wild-type site. Although this boundary region is essential for dimer resolution, its DNA sequence is poorly conserved among multimer resolution sites in related plasmids. We present evidence that its function is to influence the three-dimensional organization of the site and suggest that it may be required for the formation of a condensed nucleoprotein complex.